THE PROBLEM OF ARTISTIC COMPOSITION IN UZBEK LITERATURE (American Journal of Interdisciplinary Research and Development, 2025)
The article analyzes the essence of the composition of a work of art, its connection with the harmony of form and content. The interpretation of the concept of composition in various approaches to literary criticism is considered, the views of various scientists are studied. The elements that make up the composition of the work, the connection of the composition with the plot and its importance for ensuring artistic integrity are highlighted. Uzbek literary studies also analyzes research on the theory of composition, approaches in scientific sources, and draws important conclusions.